2023
DOI: 10.1101/2023.08.10.552787
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Residence-colonization trade-off and niche differentiation enable the coexistence ofEscherichia coliphylogroups in healthy humans

Thibaut Morel-Journel,
Sonja Lehtinen,
Olivier Cotto
et al.

Abstract: Despite the extensive literature on the pathogenicity and virulence of the commensal bacterial species and major pathogen Escherichia coli, much less is known about its natural ecological and evolutionary dynamics in populations of healthy hosts. Based on remarkably detailed longitudinal data on the gut microbiota of eight healthy individuals over months to years, we identified a trade-off between colonization and persistence, with major E. coli strains (phylogroups) exhibiting a diversity of strategy from str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…A re-analysis of the data from Martinson and Walk [49] showed that the long persistence of some phylogroups was counterbalanced by a poorer capacity to colonize hosts. This persistence-colonization trade-off, together with an additional mechanism of niche differentiation, could in theory explain the coexistence of multiple E. coli phylogroups in the population [75].…”
Section: Discussionmentioning
confidence: 99%
“…A re-analysis of the data from Martinson and Walk [49] showed that the long persistence of some phylogroups was counterbalanced by a poorer capacity to colonize hosts. This persistence-colonization trade-off, together with an additional mechanism of niche differentiation, could in theory explain the coexistence of multiple E. coli phylogroups in the population [75].…”
Section: Discussionmentioning
confidence: 99%